Affordability of Public Transport in Developing Countries - Carruthers, Robin; Dick, Malise; Saurkar, Anuja (World Bank, Washington, DC, 2014)
The analysis reported here was prompted by a realization that there was little reliable and consistent information on what proportion of household income is spent on urban public transport. The information available uses inconsistent definitions of what costs are included and how income is measured, making comparisons between cities difficult. The authors report here on about a dozen studies that have addressed the issue of affordability. Though different measures are used in different countries, making it difficult to compare the results between cities, from the studies in South America, South Asia, Eastern and Western Europe, Africa, East Asia and Australasia summarized here, the authors make clear that the affordability of urban transport is considered an issue of importance throughout the developing world. There is also evidence that the high cost of urban transport is having a negative impact on the lives of the urban poor - either through restricting their access to jobs that are within feasible walking or cycling distance, by consuming an unsustainable proportion of their income, or by dramatically curtailing the number of journeys that they make. The problem is possibly most grave in Africa, the continent for which there is the least documentation. To address the need for easily available and comprehensive comparative information on affordability of public transport fares, the authors developed an Affordability Index to be used as a first indication of the affordability of fares in a particular city. The second half of this report describes the construction of this Affordability Index and then describes the results from applying this Index to 27 cities.